Reticulocyte Hemoglobin Equivalent (Ret-He) sebagai Parameter Defisiensi Besi pada Bayi dan Anak - Lina Purnamasari (PT Kalbe Farma Tbk., 2024)
Iron deficiency and iron deficiency anemia are still health problems in infants and children around the world, including in Indonesia. There are many causal factors, including pregnancy, rapid growth, nutrition, disease, socioeconomics, etc. The impacts of iron deficiency or iron deficiency anemia include neurological disorders, growth, development, immunity, etc. Early detection is very important, one of the parameters of iron deficiency is Ret-He.